Hubungan Pengetahuan Ibu Hamil Dengan Kejadian Hiperemesis Gravidarum Di Praktek Bidan Fina Sembiring Sari Rejo Kecamatan Medan Polonia Kota Medan Tahun 2022 - Sonia Novita Sari; Ariska Fauzianty; Friza Novita Sari Situmorang; Yesica Geovany Sianipar (Jurnal Sains dan Kesehatan, 2022)
Hyperemesis gravidarum (HEG) is a condition of persistent vomiting in pregnancy that causes various disturbances in the body's balance such as dehydration, electrolyte disturbances, metabolic and nutritional deficiencies and can even cause death. This study aims to determine the relationship between knowledge of pregnant women and the incidence of hyperemesis gravidarum at Fina Sembiring Midwife Practice Sari Rejo Clinic, Medan Polonia District, Medan City. This research is an analytical quantitative research using a cross sectional design. The population in this study were all pregnant women who made pregnancy visits at the Fina Sembiring Clinic in 2022, totaling 45 pregnant women. The sampling technique is total sampling. Data collection was analyzed by chi-square test. The results of this study indicate that there is a significant relationship between knowledge and the incidence of hyperemesis gravidarum at the Fina Sembiring Clinic with a p value <0.05 (0.002).